THE SUBTITLE STRATEGY OF SLANG TRANSLATION IN 21 JUMP STREET MOVIE FAN SUBTITLES - Mar'i Muhammad Bima Saputra (UIN Raden Mas Said Surakarta, 2021)
Abstract Slang is one of the aspects of languages that requires experience and knowledge. Some of the slang is not only for delivering certain meaning but also for identifying or expressing the speaker. Slang also appears in the subtitles of the film. Related to this case, this research aims (1) to describe types of slang that is found in 21 Jump Street movie by Original Film, (2) to describe what subtitle strategies that the subtitler used to translate the slang in 21 Jump Street movie by Original Film, and (3) to describe the relationship between the most widely used subtitling strategies and the type of slang that dominantly appears in 21 Jump Street movie. This research is descriptive qualitative research and the expert is involved in the case to validate the data analysis. There were 145 data collected. 21 data are categorized as